Pengaruh Inflasi, Kurs, dan Industri terhadap Penerimaan Pajak di Indonesia - Syahrullah, Azmi Fawwaz (Media Akuntansi Perpajakan, 2025)
This study aims to analyze the influence of the Industrial Production Index, inflation, and the rupiah exchange rate on tax revenue in Indonesia. The method used is multiple linear regression with classical assumption tests to ensure the feasibility of the model, supported by secondary time-series data processed through a quantitative approach. The results of the study show that the Industrial Production Index, inflation, and the rupiah exchange rate have a significant effect on tax revenue. Simultaneously, the three independent variables are proven to significantly influence tax revenue. The implications of this study highlight the importance of macroeconomic stability in supporting the optimization of state revenue, indicating that the government needs to maintain conducive industrial conditions and exchange rate stability. These findings may also serve as a reference for future research in developing more comprehensive tax revenue prediction models.